PASSIONATE RELIGIOSITY AND THE NEW RELIGIOUS AWARENESS IN THE URBAN SOCIETY: A PSYCHO-SOCIAL STUDY - Hafidz, Hafidz; Munir, Akhmad (UIN Kiai Haji Achmad Siddiq Jember, 2022)
Today, the religious expression of the urban community looks passionate. This religious passion can be seen in worship manifested in caring for others, charity (infaq, sadaqah), and a shar'i lifestyle in the public sphere. However, on the other hand, this new enthusiasm for religion has created a new awareness of religion. This article investigates the phenomenon of passionate religion in Lumajang and Jember East Java using psycho-social studies with phenomenological interpretation analysis. The result is that the new religious passion is determined by religious knowledge, practice, and experience, which are constructed gradually over time. This awareness is then dynamically reflected and embodied in a pluralistic social life. This passionate religious expression has complex psycho-social factors in Muslim society due to different social interactions, individually and in groups. This phenomenon, firstly, is triggered by an understanding of religion that is more on the aspect of theology (spiritual aspects) than a hard-and-fast understanding of religion (the formal aspect of fiqh and sharia). Second, the people are disappointed with religious figures and institutions that only teach religious doctrines, not values and substance. Third, the social community and religious education do not encourage inclusive, reflective, and critical views on social issues.